Pengaruh Incorporating Progressive Muscle Relaxation dan Diaphragm Breathing Exercise terhadap Aliran Puncak Ekspirasi Pasien Asma - Keristina Ajul; Yakobus Siswadi; Wilhelmus Hary Susilo (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Asthma is a disorder in the form of chronic inflammation of the airways, resulting in the narrowing of the airways, thereby increasing resistance to airflow and decreasing the expiratory flow rate. Asthma management is not only pharmacological but also non-pharmacological. The latter includes exercises incorporating progressive muscle relaxation and diaphragm breathing exercise which can increase peak expiratory flow. The aim of this study was to determine the effect of incorporating progressive muscle relaxation and diaphragm breathing exercise on the increase in peak expiratory flow (PEF) of asthma patients. The research method was quasy experimental pre-test and post-test with control group. The number of research respondents was 80 people, divided into 2 groups, namely 60 people in the intervention group and 20 people in the control group. The results of the paired sample t-test difference in the intervention group showed a significant difference in PEF before and after the intervention (65.05% vs 81.17%, p = 0.00). The results of the independent t-test showed a significant difference between the PEF of the intervention group and the control group (81.17% vs 65.10%, p = 0.00). In conclusion, incorporating progressive muscle relaxation and diaphragm breathing exercise has an effect on the improvement of PEF.